Sistema de medición de estrés - Acevedo M, María E.; Acevedo M, Marco A.; de Luca P, Adriano (Revista Mexicana de Ingenieria Biomedica, 2001)
This work presents the design of a digital system to be able to determinate the level of stress in a person by implementing the direct and integral "Stress-Comfort" scale. This scale have seven parameters whose partial values are added to obtain the level of stress in a human being. The seven parameters are: Respiration, Posture, Muscle Tensión (EMG), Skin Conductivity (GSR), Cortisol and Prolactin, and the Test of the Measure of Psychological Stress (MSP). The EMG, GSR, and Respiration parameters are measured directly from the patient body through sensors. The signal of these sensors are convert first, in analogical voltage and then, this voltage is converted into digital signals by means of a personal computer (PC), that capture and process them. These results are shown both numerically and graphically and they could be printed. This work proposes an electronic circuit that use infrared devices to sense the thorax and abdominal respiratory movement without putting anything around the human body.